The effect of the Tax Reform Act of 1986 on the location of assets in financial services firms - Altshuler, Rosanne; Hubbard, R. Glenn 1958- (NBER working paper series, 2000)
This paper examines the effects of the Tax Reform Act of 1986 on the international location decisions of U.S. financial services firms. The Act included rule changes that made it substantially more difficult for U.S. firms to defer U.S. taxes on overseas financial services income held in low-tax jurisdictions. These same rule changes were not applied to other forms of income; in particular, income generated from active manufacturing operations was still eligible for deferral after the Act. We use information from the tax returns of U.S. corporations to examine how local taxes affect the allocation of assets held abroad. We find that, before the Act, the location of assets in financial subsidiaries was responsive to differences in host country tax rates across jurisdictions. However, after the Act, differences in host country tax rates no longer explain the distribution of assets held in financial services subsidiaries abroad. In contrast, we find that assets held in manufacturing subsidiaries have become more sensitive to variations in tax rates. Our results suggest that the tightening of the anti-deferral provisions applicable to financial services companies has been successful in neutralizing the effect of host country income taxes on investment location decisions.